Economic policies and their ability to reform the investment climate Case Study Iraq after 2003 - عبد الوهاب, إكرام عبد العزيز (Journal of Economics and Administrative Sciences, 2020)
The investment climate is the main engine of economic development. If an appropriate and attractive investment climate is created that takes into account economic, administrative, political and environmental issues, it will contribute to the development of industry, transfer of technology, diversification of agricultural production, increased productivity, the promotion of a green economy and support for sustainable and inclusive growth. Thus, analyzing the investment climate of a country can provide reasons and roots for the complexity of the problems in the economy. In the Iraqi economy, the problem has not been rooted in the economy, but the roots of the problem are deeper and inherent in the management of the economy. Investment in Iraq suffers from an irrational administration that has been reflected in complex imbalances in the Iraqi economy, thus creating an environment for expelling investment. In light of the foregoing, the research assumes that there are administrative, security, financial and monetary constraints, as well as the spread of corruption in all forms, which have hindered the expansion of the scope of investment and the diversity of its tracks due to its impact on the investment environment. The research has proved this hypothesis, in addition to improving the investment climate, depends on changing the overall methodology of administrative and economic policies, financial, monetary and how to coordinate with each other effectively. The research also found that the main reason for the poor management of the economy is the almost total absence of the pillars of good governance because of the negative factors that put pressure on it. And this led to the lack of a clear policy adopted by the government to improve the investment climate, national development plans have not been ratified by parliament and many of the strategies approved by the government lacked the appropriate mechanisms to implement them, therefore, the most important recommendation by the research is to instill and stabilize the basis of accountability rules, elements And their controls in the institutional environment, before any reform is initiated; in order to correct the course of macroeconomic management.